Global temporal trends and projections of gastroesophageal reflux disease prevalence: Age-period-cohort analysis 2021 - Feng Xie; Baoqin Yang; Zeng Yan; Yong Shen; Hui Qin; Li Chen; Tiantian Chen; Jigui Chen; Shaihong Zhu; Fei Xiong; Xulong Sun (PLoS ONE, 2025)
Background Gastroesophageal reflux disease (GERD) represents a major global health challenge with varied regional epidemiological patterns. This study aimed to comprehensively analyze temporal trends, health inequalities, and driving factors of GERD. Methods Using Global Burden of Disease 2021 data, we extracted GERD prevalence across 204 territories. Age-standardized prevalence rate (ASPR) was calculated and analyzed using age-period-cohort framework. An autoregressive integrated moving average model was employed to project future trends to 2036. Health inequalities were assessed using slope index and concentration index. Results Global GERD prevalence surged from 450,765,455 cases in 1990–825,603,654 in 2021, with an annual percentage change of 0.04% in ASPR. Significant regional disparities were observed across Socio-demographic Index (SDI) quintiles: middle SDI regions exhibited the steepest ASPR increase (0.22% annually), contrasting with declining trends in high-middle (−0.26%) and high SDI regions (−0.18%). Latin American countries demonstrated the highest burden, with Paraguay, Brazil, and El Salvador leading globally. The United States and China revealed notable post-2010 prevalence rebounds. Notably, populations aged 25–34 years showed the most rapid prevalence growth (>0.3% annually), challenging traditional age-risk paradigms. The slope index increased from −1978.5 to −2053.4, signifying worsening absolute health disparities, with low SDI nations bearing a disproportionate GERD burden. Conclusions The increasing prevalence of GERD has resulted in major health burdens over the past three decades. Future strategies should prioritize targeted interventions for high-risk populations and modifiable risk factors, enhanced healthcare accessibility, and integration of GERD management within non-communicable disease frameworks to address this emerging public health challenge.